Facile Synthesis of a Water-Soluble Cobalt Phthalocyanine Derivative - Cong, Fangdi; Wang, Xiuyan; Gao, Gui; Du, Xiguang; Wei, Zhen; Yu, Fengyang; Wang, Junbin; Yu, Guojing; Chen, Bin; Xing, Kezhi (Asian Journal of Chemistry, 2010)
The water-soluble tetra-β-carboxymethyleneaminophthalocyanine cobalt is synthesized, in one step, from tetra-β-aminophthalocyanine cobalt. The synthesized compound, as a catalyst in oxidation of sulfide, behaves enhanced catalytic activity relative to tetra-β-carboxyphthalocyanine cobalt.